(untitled) (Principles and Practice of Clinical Research, 2021)
Fibromyalgia (FM) is a functional syndrome characterized by musculoskeletal, diffuse and persistent (> 3 months) chronic pain, that is also characterized by sleep disturbances, fatigue, humor changes and cognitive and psychological changes. Transcranial Pulsed Current Stimulation (tPCS) is a new Transcranial Electrical Stimulation (tES) that has been studied as a treatment option for chronic pain and neurological conditions . Studies have shown that tPCS is capable of pain and cognitive modulation; however, there are not enough studies with evidence of its efficacy.Therefore, the primary aim of this study is to evaluate the effects of tPCS in pain, evaluated through Visual Analogue Scale (VAS) in FM patients; besides that, it is aimed to evaluate the effects of tPCS on quality of life, cognitive impairments, pain pressure threshold, descending inhibitory system of pain, and serum levels of Brain Derived Neurotrophic Factor (BDNF) and S100 Calcium-Binding Protein B (S100B). A randomized, double-blinded, controlled with sham clinical trial will be conducted with 70 (Critical f: 2.003; ES: 0.76; alpha: 0.05; power: 0.80) women with Fibromyalgia, from 30 to 65 years with pain on the Visual Analogue Scale (VAS) higher than 6 in the last 3 months. All patients will read and sign an Informed Consent Form (ICF). Each patient will be randomized to either 1+4 sessions of tPCS (2mA, 6-10Hz, 1-20ms, 20-25 minutes) or Sham. Patients will complete the following questionnaires/tests: Visual Analogue Scale (VAS), Pittsburgh Sleep Quality Index (PSQI), Fibromyalgia Impact Questionnaire (FIQ), Pain Catastrophizing Scale (PCS), Profile of Chronic Pain (PCP), Conditioned Pain Modulation Task (CPM-T), Pain Pressure Threshold Task (PPT-T), Rey Auditory-Verbal Learning Test (RAVLT), Controlled Oral Word Association Test (COWAT) and blood collection for serum levels of BDNF and S100B. For the main outcome, comparison between variables during time will be made through linear regression, with an adjustment for baseline levels and possible confounders.